(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In the modern world, investment projects are the most important tools for programtarget management, in the development and implementation of which the most significant aspect that determines the final result is an effective risk management system. The article discusses the features of domestic and foreign risk management practices for investment projects that have developed in the modern management environment. The theoretical and practical foundations of various methods and techniques for assessing the risks of investment projects and tools for minimizing them are analyzed. Based on the analysis of the application of methods for assessing the risks of investment projects, recommendations were developed to improve the Russian practice of their use.